Un poema de Verdaguer inèdit i censurat. Notes a propòsit del llibre Disperses (1924). - TORRENTS, RAMON PINYOL I. (Scripta, 2023)
Among Verdaguer's remaining unpublished manuscripts is a set prepared by Lluís Carles Viada i Lluch, which was commissioned by Francesc Matheu for the volume Disperses (1924) of The Complete Works of Jacint Verdaguer, and published in La Ilustració Catalana. Matheu, however, considered it inappropriate to publish most of the poems, probably because they belonged to the time of conflict with the hierarchy, were too incisive and, in some cases, directly alluded to specific people (Marquis of Comillas, Bishop Morgades, Canon Jaume Collell, cousin Narcís Verdaguer i Callís). Matheu kept Viada's transcriptions among his papers. In the process of critical edition, today we are publishing a contextualised representative sample of special interest of Verdaguer's opus.